Problems and Challenges to Determine Pesticide Residues in Nepal - Raj Bhattarai, Bibek; Aryal, Babita; Adhikari, Bikash; Parajuli, Niranjan (International Journal of Environment, 2019)
Nepal is predominately an agrarian country where still the majority of the total population rely on agriculture (Adhikari, 2018). The productivity of agriculture should be augmented to fulfill the increasing demand for food. Despite countless efforts, the agriculture sector could not come across to accomplish the global market for foodstuffs due to climate change. By which, plants will be attacked by various insects, funguses, and microorganisms. To tackle such problems, pesticides are being widely used to defend and block agriculture products from harmful organisms. But due to lack of public awareness, large numbers of farmers have been using pesticides as medicine - a conviction implanted in their mind (Pingali et al., 1995).